Goffman in Dixon. Ethnographer or Performer? - Romania, Vincenzo (Italian Sociological Review, 2019)
In this article I analyse a little-known part of Erving Goffman’s production: his doctoral dissertation Communication Conduct in an Island Community (1953). I will consider in particular the methodological aspects of the research and the characteristics of the community studied. The article aims at demonstrating how the methodological discussion of this early work is so accurate, extensive and consistent with the ethnographical canon of the time to allow deconstructing of two typical criticism moved to Goffman: a) the lack of transparency in the specification of the methods of data collection; and b) the loose relationship between data collection and theoretical argumentations (for a review see Lemert, 1997).